Co-occupations: The caregiving challenges of mothers of children with cerebral palsy. (July 2015) - Dalvand, Hamid; Hosseini, Seyyed Ali; Rassafiani, Mehdi; Samadi, Sayyed Ali; Khankeh, Hamid Reza; Kelly, Greg
Introduction: This study was conducted in an Iranian context to explore the co-occupations of mothers of children with cerebral palsy as experienced by them. Method: This qualitative study was conducted using content analysis methodology. Sixteen mothers of children with cerebral palsy participated in the study. Data was collected via in-depth, semi-structured interviews. Constant comparative analysis was deployed for data analysis. Results: The results were classified into nine sub-categories and four main categories that were identified as (1) coping with self-care problems, (2) effort to gain treatment follow-up, (3) coping challenges of educational care, and (4) limited parental personal leisure time. Conclusion: Understanding the challenges of caring for a child with cerebral palsy and the experiences of mothers when engaging in co-occupations with their child, provides a broader perspective of the potential impact on participation and engagement of mothers. However, more research is required to understand the various factors influencing participation and co-occupations and interaction effects between these factors.